Research on high-resolution water pollutant source list of Daqing River Basin (Baiyangdian). Issue 1 (August 2020) - Bian, Wei; Wang, Mingxiao; Liu, Yuan; Zhang, Jingwei; Li, Ruihong; Zhao, Na; Hao, Mingliang
Abstract: With the refinement of water environment management in the basin, the work of Water Pollutant Source List (WPSL) has been carried out. The article separately calculates the pollution load of point sources and area sources, among which point sources include industry sources, sewage treatment plants, large-scale livestock and poultry farms, area sources include urban runoff, rural life, agricultural planting, and rural livestock and poultry farming. Pollutants include chemical oxygen demand (COD), ammonia nitrogen (NH3 -N), total nitrogen (TN), and total phosphorus (TP). Based on a certain spatial induction method, the pollution load is assigned to a grid of 1km×1km, and a high-resolution water pollution source list is established, which provides a refined basic database for environmental management.